Proceedings of the ACM Symposium on Applied Perception 2014
DOI: 10.1145/2628257.2628264
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating affective features of 3D motionscapes

Abstract: motion textures are widely applied in visual design and immersive environments such as games to imbue the environment or presentation with affect. While visual designers and artists carefully manipulate visual elements such as colour, form and motion to evoke affect, understanding what aspects of motion contribute to this still remains a matter of designer craft rather than validated principle. We report an empirical study of how simple features of motion in 3D textures, or motionscapes, contribute to the elic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 29 publications
2
11
0
Order By: Relevance
“…Animation can play a role in visual discourse and storytelling [CRP16], and animated transitions help show state changes between two different graphics, such as changing the viewport and showing dynamic timesteps [HR07]. In studies on animated transitions, Heer and Robertson show animation's effectiveness for tracking objects [HR07], Feng et al highlight how motion changes a person's affect [FBR14], Chang and Ungar argue that animation can increase user engagement for interfaces [CU95], and Chevalier et al found that animating text vertically helps with reading more than page‐flipping animations [CDBF10]. Animations can fail due to the apprehension principle [TMB02], and these detriments may be offset using interaction [TMB02], such as by linking animation to clicking or scrolling.…”
Section: Related Workmentioning
confidence: 99%
“…Animation can play a role in visual discourse and storytelling [CRP16], and animated transitions help show state changes between two different graphics, such as changing the viewport and showing dynamic timesteps [HR07]. In studies on animated transitions, Heer and Robertson show animation's effectiveness for tracking objects [HR07], Feng et al highlight how motion changes a person's affect [FBR14], Chang and Ungar argue that animation can increase user engagement for interfaces [CU95], and Chevalier et al found that animating text vertically helps with reading more than page‐flipping animations [CDBF10]. Animations can fail due to the apprehension principle [TMB02], and these detriments may be offset using interaction [TMB02], such as by linking animation to clicking or scrolling.…”
Section: Related Workmentioning
confidence: 99%
“…Some of these additional properties are speed, motion shape, direction, and path curvature. Fast-moving objects are associated with higher arousal than slow-moving objects (Feng et al, 2014;Piwek et al, 2015). But there are contradictory findings regarding the type of valence associated with speed.…”
Section: Visual Cuesmentioning
confidence: 96%
“…But there are contradictory findings regarding the type of valence associated with speed. One study suggest that fast movements are related to positive affective states (Piwek et al, 2015), while other study indicates the opposite (Feng et al, 2014).…”
Section: Visual Cuesmentioning
confidence: 99%
“…Narrative visualizations aim to increase user engagement and evoke affective responses [3], [6]. Affect matters for communicative intent and engagement [3], [6] and plays important roles in visualization [14]- [17]. Eliciting affective states enhances problem solving and reduces boredom and frustration [14], [18].…”
Section: Affect and Experience In Visualizationmentioning
confidence: 99%